2013
DOI: 10.1007/s00223-013-9784-9
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Phosphate Mineral Nucleation in Biology and Geobiology

Abstract: Relationships between geological phosphorite deposition and biological apatite nucleation have often been overlooked. However, similarities in biological apatite and phosphorite mineralogy suggest that their chemical formation mechanisms may be similar. This review serves to draw parallels between two newly described phosphorite mineralization processes, and proposes a similar novel mechanism for biologically controlled apatite mineral nucleation. This mechanism integrates polyphosphate biochemistry with cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 146 publications
(183 reference statements)
1
47
0
1
Order By: Relevance
“…In addition, other functional roles have been attributed to apatite biominerals like homeostasis or the inactivation of toxic elements. Several reviews have been published on this subject with different approaches focusing on crystal structures, and calcium phosphate precursors [6], the role of OH-channels [7], the role of unstable amorphous precursors [8], the role of polyphosphates [9], general view including the organic matrices [10], apatite biominerals and biomimetic processing and materials [11], and mineralogical oriented reviews [12]. This review aims to present and discuss the specific characteristics of biomineral apatites and illustrate how these characteristics and the resulting mineral properties have been employed in the adaptation for specific biological functions, in the case of vertebrate hard tissues (bone, dentine and enamel).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other functional roles have been attributed to apatite biominerals like homeostasis or the inactivation of toxic elements. Several reviews have been published on this subject with different approaches focusing on crystal structures, and calcium phosphate precursors [6], the role of OH-channels [7], the role of unstable amorphous precursors [8], the role of polyphosphates [9], general view including the organic matrices [10], apatite biominerals and biomimetic processing and materials [11], and mineralogical oriented reviews [12]. This review aims to present and discuss the specific characteristics of biomineral apatites and illustrate how these characteristics and the resulting mineral properties have been employed in the adaptation for specific biological functions, in the case of vertebrate hard tissues (bone, dentine and enamel).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial processes may play a role in phosphatization of faunal remains and phosphatic mineral deposits [63,64], but possible involvement of microbes during phosphatization of wood has not been studied. Previous reports provide abundant evidence for the recognition of microbial associations in aquatic mineral deposits where mineral deposition is facilitated by microbial mats or biofilms.…”
Section: Mineralization Processmentioning
confidence: 99%
“…Extracellular polyphosphate (polyPi, an extended analogue of PPi) also serves in the transport and compartmentalization of phosphates 22 . In the same way that glucose concentration is controlled by formation and destruction of glycogen, Pi concentration is regulated by formation and destruction of polyPi -a substrate for enzymatic cleavage in the skeleton 23 . PolyPi-packed granules chelate calcium ions, forming neutrally charged and amorphous complexes 23 ; thus it seems that calcium-binding PPi and polyPi are a bioreservoir of mineral ions and effectively preclude collagen-based soft tissues from undesired mineralization.…”
Section: General Inhibition Selective Promotion and Selective Inhibimentioning
confidence: 99%
“…In soft tissues not destined for mineralization, the ratio of PPi/Pi remains high to inhibit mineralization. It has been suggested that polyPi granules contain alkaline phosphatase and other proteins; the notion here being that if alkaline phosphatase is activated, hydroxyapatite nucleates within the granule, displaces the protein component to the granule surface to result in the formation of a crystalline core coated with an amorphous shell 23 .…”
Section: General Inhibition Selective Promotion and Selective Inhibimentioning
confidence: 99%